Clinicopathologic and Prognostic Significance of Multiple Hormone Expression in Pancreatic Neuroendocrine Tumors. (May 2015) - Kim, Joo Young; Kim, Min-Sun; Kim, Ki-Suk; Song, Ki-Byung; Lee, Seung Hun; Hwang, Dae Wook; Kim, Kyu-pyo; Kim, Hyoung Jung; Yu, Eunsil; Kim, Song Cheol; Jang, Hyeung-Jin; Hong, Seung-Mo
Abstract : Pancreatic neuroendocrine tumors (PanNETs) produce variable peptide hormones. The expression status of some hormones has been linked to the biological and clinical behaviors of PanNETs. A total of 226 surgically resected PanNETs were selected. Immunolabeling for peptide hormones was compared with various clinicopathologic factors, including patient survival. Expression of insulin, glucagon-like peptide 1, glucagon, gastrin, somatostatin, and serotonin were observed in 56 (24.8%), 41 (18.1%), 25 (11.1%), 5 (2.2%), 5 (2.2%), and 4 (1.8%) cases, respectively. Expression of 1, 2, and 3 hormones was noted in 70 (31.0%), 28 (12.4%), and 3 (1.3%) cases, respectively; 125 cases (55.3%) were negative for all hormones. PanNETs with insulin and glucagon-like peptide 1 expression were associated with a lower grade, smaller size, lower pT and pN classifications, absence of lymphovascular invasion, and lymph node metastasis and had better survival by univariate analysis, whereas PanNETs with gastrin expression were associated with a higher grade, larger size, higher pT and pN classifications, presence of lymphovascular invasion, and lymph node metastasis and had worse survival. Gastrin expression, increased age, and tumor grade were negative prognostic factors in multivariate analysis. As the number of hormones expressed increased, the survival rate of PanNET patients increased. In summary, PanNET patients showing insulin or glucagon-like peptide 1 expression and increased numbers of expressed hormones had a better survival outcome by univariate analysis, whereas gastrin expression was a negative prognostic indicator in surgically resected PanNET patients.